DOI: 10.18174/502357
|View full text |Cite
|
Sign up to set email alerts
|

Black soldier fly larvae as a sustainable animal feed ingredient in Kenya

Abstract: Table of contents Chapter 1 General introduction Chapter 2 Insects for sustainable animal feed: inclusive business models involving smallholder farmers Chapter 3 Knowledge and willingness of smallholder farmers in Kenya to pay for insect-based feeds Chapter 4 Effects of waste stream combinations from brewing industry on performance of black soldier fly Hermetia illucens (Diptera: Stratiomyidae) Chapter 5 Threshold temperatures and thermal requirements of black soldier fly Hermetia illucens: Implications for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 193 publications
(314 reference statements)
1
4
0
Order By: Relevance
“…The feed intake and feed costs were significantly higher for the CN diet than the other diets, and consequently, the economic feed conversion ratio of the CN diet was also the highest causing a higher break-even yield. This study confirms that the use of BSFL and CN as alternative sources of protein increases the profitability of fish farming, which concurs with the results of other studies that worked with fish (Mugo-Bundi et al, 2015;Ngugi et al, 2016;Onsongo et al, 2018;Chia, 2019;Shit, 2021;Wachira et al, 2021;Çetingül and Shah, 2022;Limbu et al, 2022). Interestingly, it has further been demonstrated that utilization of CN can effectively substitute up to 75% of fish meal without compromising growth performance, survival, nutrient utilization and economic benefits, however, when substitution was as high as 100%, the performances declined (Mugo-Bundi et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The feed intake and feed costs were significantly higher for the CN diet than the other diets, and consequently, the economic feed conversion ratio of the CN diet was also the highest causing a higher break-even yield. This study confirms that the use of BSFL and CN as alternative sources of protein increases the profitability of fish farming, which concurs with the results of other studies that worked with fish (Mugo-Bundi et al, 2015;Ngugi et al, 2016;Onsongo et al, 2018;Chia, 2019;Shit, 2021;Wachira et al, 2021;Çetingül and Shah, 2022;Limbu et al, 2022). Interestingly, it has further been demonstrated that utilization of CN can effectively substitute up to 75% of fish meal without compromising growth performance, survival, nutrient utilization and economic benefits, however, when substitution was as high as 100%, the performances declined (Mugo-Bundi et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Major protein source ingredients like soybean and fish meal are often of low quality, very expensive for smallholder fish farmers (Opiyo et al, 2018;, or imported from distant less sustainable sources (Chianu et al, 2008;Abro et al, 2020). In Kenya, many initiatives have recently been started to culture black soldier fly (Hermetia illucens) larvae (BSFL), both at small and large scales (Chia, 2019). In most cases, the BSFL are cultured on locally available organic agricultural and food byproducts which otherwise are disposed in landfills.…”
Section: Introductionmentioning
confidence: 99%
“…According to Holmes et al (2013), the pupation stage of BSF larvae was carried out without a substrate to reduce threats from the environment, which lasted the shortest time. However, the hatching rate from pupae to adults was lower than those using other substrates (i.e., sawdust, soil, humus, and sand) (Chia, 2019).…”
Section: B Larval Phasementioning
confidence: 69%
“…In the larval phase, BSF insects can be classified into 6 instars (Chia, 2019). Instar is a period of change or renewal of the larva's outer tissue (exoskeleton).…”
Section: Bsf Larvaementioning
confidence: 99%
“…The dry or wet BSFL can be harvested and fed to animals without further processing [ 10 ]. In addition, BSFL is considered not to be a pest or vector of any diseases and, therefore, does not cause any significant nuisance [ 11 ]. BSFL grease is a suitable raw material to produce biodiesel [ 12 ].…”
Section: Introductionmentioning
confidence: 99%